PENGEMBANGAN LKPD BERBASIS NILAI-NILAI ISLAM UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA KELAS 3 SD - Markhamah, Mona; Andini, Wulan; Arifuddin, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The numeracy literacy ability of elementary school students in Indonesia is still relatively low, as reflected in the 2022 PISA results which show that the average mathematics score of Indonesian students only reaches 366 points, far below the OECD average of 472 points. This condition encourages the need to develop innovative teaching materials that not only support the achievement of academic competence, but also shape the character of students. This research aims to develop a Student Worksheet (LKPD) based on Islamic values that is valid, practical, and effective in improving the numeracy literacy skills of 3rd grade students of SDN Samadikun. The method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Data was collected through interviews, observations, expert validation questionnaires, student and teacher response questionnaires, and pretest-posttest tests. The results of the study showed that the LKPD developed obtained a very valid category from teaching material experts (81.33%), linguists (90.67%), and material experts (93.33%). The level of practicality of the product reached the very practical category based on the responses of students (90.86%) and teachers (95.29%). The effectiveness of the product was proven by an increase in the average pretest score from 61.93 to 82.59 in the posttest, with an N-Gain value of 54.05% (medium category), and strengthened by the results of the Paired Samples T-Test with a significance value of 0.000 < 0.05. It was concluded that LKPD based on Islamic values is suitable for use as innovative teaching materials in mathematics learning in elementary schools.